CHARACTER EDUCATION FROM THE PERSPECTIVES OF ELEMENTARY SCHOOL PHYSICAL EDUCATION TEACHERS - Tatang Muhtar; Ruswan Dallyono (Jurnal Cakrawala Pendidikan, 2020)
Physical Education (PE) in elementary schools has so far been extensively geared towards achieving character goals. However, not all of these goals have been well accomplished by teachers. This research aims to examine three fundamental issues in PE practice, i.e., to define PE teachers perceptions of character education, to identify problems of PE teachers in promoting character education, and to determine whether PE teachers consider character education is plausible to be implemented through PE activities. This study used a case study and a content analysis in the qualitative research method. The data were obtained from 53 PE teachers who worked in 53 elementary schools from 26 sub-districts in Sumedang Regency through an accessible case sampling method. This study employed individual interviews (10-15 minutes) in a semi-structured interview technique. Content analysis was used to analyze the interview scripts. This study revealed that character education is defined as the process of individual alteration from family, school, and social life. Meanwhile, the teachers stated that the curriculum is considered to be not precisely accessible for the development of character education since they were still confused about curriculum implementation. However, they believed that PE is effective to promote character education.